2018
DOI: 10.4081/ripppo.2018.297
|View full text |Cite
|
Sign up to set email alerts
|

An integrated approach to child psychotherapy with co-parental support: a longitudinal outcome study

Abstract: Studies about the effectiveness of psychodynamic psychotherapy interventions with children and adolescents suggest potential adverse effects of this treatment when not supported by a parallel work with parents: it seems that it could damage family functioning and affect family balances. This research aims to assess psychopathological outcomes after two years of psychodynamic psychotherapy by comparing two groups (G) of children and adolescents, related to a Childhood Adolescence Family Service: G1 – individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…In short, the participants appeared to benefit from the therapy. Our results are consistent with previous studies ( Beutler et al, 2012 ; Miscioscia et al, 2018 ) that have noted the effectiveness of integrated psychotherapy. The FBIM follows this tradition by proposing an approach that integrates a psychodynamic reading of the patient’s functioning.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In short, the participants appeared to benefit from the therapy. Our results are consistent with previous studies ( Beutler et al, 2012 ; Miscioscia et al, 2018 ) that have noted the effectiveness of integrated psychotherapy. The FBIM follows this tradition by proposing an approach that integrates a psychodynamic reading of the patient’s functioning.…”
Section: Discussionsupporting
confidence: 93%
“…The literature on integrated psychotherapies has grown considerably ( Feldman and Feldman, 2005 ). Several studies have demonstrated the effectiveness of integrated approaches ( Beutler et al, 2012 ; Miscioscia et al, 2018 ). In Schottenbauer et al’s (2005) review, nine studies showed substantial support, 13, some support, and seven, preliminary support.…”
Section: Introductionmentioning
confidence: 99%
“…The present project (approved by the local ethical committee-CEP 204 SC) was based on the above-mentioned premises, giving important consideration to the family household during the process of a patient's referral into the Service. The therapeutic approach involving the parents in the treatment considers the family as a structured subsystem and a composite set of different functions and roles, amongst which the roles of parenting, co-parenting, etc (35,36).…”
Section: Aimsmentioning
confidence: 99%